Barcellona è pronta per FOSS4G 2010 (GEOmedia, 2010)
FOSS4G 2010FOSS4G is "the conference" for Open Source Geospatial Software and on september 2010 will meet in Barcelona, Spain. At FOSS4G you will meet all kind of actors: Free Software developers and any kind of representatives from companies, institutions and the academic world. The spatial industry is undergoing rapid innovations and the open source spatial community is one of the forces driving the change.